Portrait of Poverty in the Novel of Gadis Pesisir by Nunuk Y. Kusmiana (Study of Literature Sociology) - Nur Inayah; Nensilianti Nensilianti; Hajrah Hajrah (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. This study aims to describe the form of poverty in the novel Gadis Pesisir using theory of sociology of literature. This study uses a qualitative approach with descriptive research type, the researcher describes the data on the form of poverty on social life. The data in this study are words, sentences, and paragraphs that reveal the form of poverty and the influence of poverty on social life. Data source in this study is the novel Gadis Pesisir by Nunuk Y. Kusmiana published by Gramedia Pustaka Utama in 2019 with a book thickness of 321 pages. Data collection techniques in this study are reading and note-taking techniques, through analysis techniques, namely data identification, data classification, data analysis and interpretation, and drawing conclusions. The results showed that the portrait of poverty contained in the novel Gadis Pesisir is the inability to meet basic consumption (clothing, food, and housing), lack of access to other basic necessities of life (health, education, sanitation, clean water, and transportation), lack of security for life future (due to the lack of investment in education and family), vulnerability to individual and mass shock, low quality of human resources and limited natural resources, occurrence of physical or mental disability, and social disability and disadvantage. Keywords: Poverty, Portraits Of Poverty, Sociology Of Literature.